Definitive treatment of primary vaginal cancer with radiotherapy: multi-institutional retrospective study of the Korean Radiation Oncology Group (KROG 12-09) - Chang, Ji Hyun; Jang, Won Il; Kim, Yong Bae; Kim, Jin Hee; Kim, Young Seok; Kim, Yeon Sil; Park, Won; Kim, Juree; Yoon, Won Sup; Kim, Joo-Young; Kim, Hak Jae (Journal of gynecologic oncology, 2016)
To assess the outcome of the treatment of primary vaginal cancer using definitive radiotherapy (RT) and to evaluate the prognostic factors of survival. The medical records of nine institutions were retrospectively reviewed to find the patients with vaginal cancer treated with definitive RT with or without chemotherapy. A total of 138 patients met the inclusion criteria. None had undergone curative excision. The median follow-up time of the survivors was 77.6 months and the median survival time was 46.9 months. The 5-year overall survival, cancer-specific survival (CSS), and progression-free survival (PFS) rates were 68%, 80%, and 68.7%, respectively. In the survival analysis, the multivariate analysis showed that a lower the International Federation of Gynecology and Obstetrics (FIGO) stage and prior hysterectomy were favorable prognostic factors of CSS, and a lower FIGO stage and diagnosed prior to year 2000 were favorable prognostic factors of PFS. In the subgroup analysis of the patients with available human papillomavirus (HPV) results (n=27), no statistically significant relationship between the HPV status and recurrence or survival was found. Grade 3 or 4 acute and late toxicity were present in 16 and 9 patients, respectively. The FIGO stage and the tumor size were predictors of severe late toxicity. The data clearly showed that a higher FIGO stage was correlated with a worse survival outcome and higher severe late toxicity. Therefore, precise RT and careful observation are crucial in advanced vaginal cancer. In this study, the HPV status was not related to the survival outcome, but its further investigation is needed.